Timing of outdoor light exposure is associated with sleep-wake consolidation in community-dwelling older men - Lok, Renske; Ancoli-Israel, Sonia; Ensrud, Kristine E.; Redline, Susan; Stone, Katie L.; Zeitzer, Jamie M. (Frontiers in Sleep, 2023)
Introduction A consolidated sleep-wake pattern is essential for maintaining healthy cognition in older individuals, but many suffer from sleep fragmentation that exacerbates age-related cognitive decline and worsens overall mental and physical health. Timed light exposure (light therapy) has been explored as a countermeasure, but mixed results have been obtained. To determine whether the timing of light exposure is important for sleep-wake consolidation, we analyzed the natural light diets of a cohort of community-dwelling older men. Methods The degree of sleep-wake fragmentation and light exposure patterns were obtained over a week using wrist actigraphy. Correlations between fragmentation, light patterns, and various physical and mental health measures were examined (n = 877). Results Our findings revealed that higher sleep-wake fragmentation correlated with poorer physical and mental health and reduced cognition. Moreover, reduced daytime light exposure was associated with increased sleep-wake fragmentation. Interestingly, morning and evening light exposure (>1,000 lux) were not useful in distinguishing between low and high sleep-wake fragmentation scores, while increased afternoon light exposure showed much better discrimination. Specifically, optimal discrimination between low and high fragmentation occurred 6.7 h after habitual sleep offset. This suggests that afternoon light therapy might be more efficient in consolidating sleep and wake in older adults, particularly in those with low-amplitude circadian rhythms. Discussion This study highlights the significance of properly-timed light exposure in promoting consolidated sleep and cognitive health among older individuals. Tailored light-based strategies may have the potential to enhance physical, mental, and cognitive well-being in the aging population.